Penanaman Karakter Jujur Melalui Ujian Lisan pada Mahasiswa Manajemen Fakultas Ekonomi Universitas Muhammadiyah Semarang - Ambarsari, Arum; Masrukhi, Masrukhi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
Civic education has the aim of forming good citizens (good citizenship). One indicator of a good citizen who has an honest character. The development of globalization and the development of science and technology turned out to have several unfavorable impacts for the Indonesian nation, one of which was the degradation of honesr character. The manajemen study Program of University of Muhammadiyah Semarang has a graduate profils of Enterpreneur, Manager, Consultant, and Educator. In order to form a graduate profile, it is very necessary to have an honest character. The formation of honest character is carried out in civic education throught an oral exam. Basd on the results of interviews conducted with UNIMUS Management students, it was obtained data that based on their perspective, 87% of tudents stated thar oral exams were very good for developing honestc haracter. The reason that students conveyed throught interviews were that throught oral exam they were really required to be able to understand teori and material so that they could answer questions withoutstuttering and nervousness.